Plant Propagation - R.G. Maiti; R.G. Maiti (Ludhiana Kalyani, 2004)
This Book Is an important branch of Horticulture.
Seed Seedbed Vegetative Propagation Of Plant
Keywords: Seed, Seedbed ,Vegetative Propagation Of Plant